Sistem Pelatihan dan Pengembangan Tenaga Pendidik di SMA Plus Assaalam - Muzakki, Ahsyaf; Supendi, Pepen (Al-DYAS, 2024)
The main problem of this research is the training and development system for teaching staff at Pluss Asalaam High School. Therefore, the aim of this research is to analyze: Strategies, results, and supporting and inhibiting factors for training and development management as well as the personalities of teaching and education staff. This research is field research with a qualitative approach, from informant sources, principals and educators. The results of this research include: firstly, the training system for teaching staff at Pluss Asalaam High School has been implemented well, this can be seen from all the teaching staff who have taken part in training, at least training held by the school such as MGMP and Workshops, and Educational Courses. Second, the teaching staff development system at Pluss Asalaam High School is also running as it should. This can be seen from the fact that almost all of the teaching staff at the school are certified civil servants, some are even continuing their education to postgraduate level. With effective training and development, the learning process can be smoothed, which will make it easier for educators and students to achieve educational goals.